Evaluation on the photocatalytic degradation activity of Reactive Blue 4 using pure anatase nano-TiO2 - Emy Marlina Samsudin,; Sze, Nee Goh; Ta, Yeong Wu; Tan, Tong Ling; Sharifah Bee Abd. Hamid,; Joon, Ching Juan (Universiti Kebangsaan Malaysia, 2015)
Disposal of dye wastewater into water streams without treatment endangers human and marine lives. This work focused on the second largest class of textile dyes after azo dyes due to its high resistivity to biodegradation and high toxicity. The photocatalytic degradation of Reactive Blue 4 (RB4), an anthraquinone dye, has been investigated using pure anatase nano titanium (IV) oxide (TiO2). The dye molecules were fully degraded and the addition of hydrogen peroxide (H2O2) enhanced the photodegradation efficiency. It is found that the degradation as the hydroxyl radicals in the bulk solution is sufficient for complete mineralisation. The disappearance of the dye follows pseudo-first-order kinetics. The effect of pH, amount of photocatalyst, UV-light intensity, light source and concentration of hydrogen peroxide was ascertained.